Relationship of family management with sociodemographic aspects and children's physical dependence in neurological disorders - Gisele Weissheimer; Verônica de Azevedo Mazza; Vanessa Ferreira de Lima; Maria de Fátima Mantovani; Márcia Helena de Souza Freire; Paulo Ricardo Bittencourt Guimarães (Universidade de São Paulo, 2018)
ABSTRACT Objective: To investigate the relationship of family management with sociodemographic and physical dependence aspects of children and adolescents with neurological impairment. Method: Descriptive, cross-sectional study conducted at a child neurology center. A non-probabilistic sample was obtained from 141 family members who answered two instruments: a) Sociodemographic condition of families; b) Family Management Measure. In the statistical analysis, we used the Spearman Coefficient and the Mann Whitney Test. Results: the longer the specialized care time, the lower the identity score (rs = - 0.209, p = 0.01); the higher the effort score (rs = 0.181, p = 0.03), the family difficulty score (rs = 0.239, p = 0.001) and the impact of the disease on family life (rs = 0.213, p = 0.01). The families of children and adolescents with physical dependence for activities of daily living presented a higher score in the following dimensions: management effort (<0.001), family difficulty (p = 0.004) and perception of disease impact (p = 0.001). Conclusion: There was evidence of a correlation between management with sociodemographic and child dependence aspects, with an association between management difficulty and longer time of child and adolescent care.